1972
DOI: 10.3382/ps.0511234
|View full text |Cite
|
Sign up to set email alerts
|

Non-Protein Nitrogen Studies in Laying Hens

Abstract: Four experiments were conducted with laying hens to examine the effectiveness of non-protein nitrogen supplementation. Significant increases in egg production were obtained with three experiments employing diammonium citrate, ammonium sulfate, and diammonium phosphate as non-protein nitrogen sources. Non-essential nitrogen consumptions of hens fed diets which responded to non-protein nitrogen supplementation were below 1.4 gm./day. The non-protein nitrogen additions increased the non-essential nitrogen intakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
1

Year Published

1976
1976
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
3
3
1
Order By: Relevance
“…The values obtained are similar to those obtained by Reid et al (1972) who used ammonium sulphate as the NPN supplement. They are also in accord with those of Fernandez et al (1973) who found that the nitrogen supplied by DAP is not utilised for egg production.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The values obtained are similar to those obtained by Reid et al (1972) who used ammonium sulphate as the NPN supplement. They are also in accord with those of Fernandez et al (1973) who found that the nitrogen supplied by DAP is not utilised for egg production.…”
Section: Resultssupporting
confidence: 87%
“…These data are in accord with those of Reid et al (1972) and indicate that between 1-3 and 1*4 g of non-essential amino acid nitrogen (NEN) are needed at this level of EN consumption. On the other hand, as shown in Table 2, it is not possible to establish a relationship between EN and NEN.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Reid et al (1972) demonstrated that addition of diammonium citrate (DAC) or phosphate (DAP) to a low-protein diet based on soyabean and milo improved egg production. DAP supplementation of a similar fishmeal-based diet did not improve performance.…”
Section: Introductionmentioning
confidence: 99%